The influence of indolinoren on kidney function in conditions of water and salt load - Markina, Anna; Mishсhenko Oksana (ScienceRise: Pharmaceutical Science, 2018)
Diuretics are widely used to correct kidney disorders. In turn, the ionic composition of food, mostly sodium ions, which directly affect the excretory function of the kidneys, can act as modulators of the action of diuretics. The aim of the study was to investigate the effects of the new 2-oxoindoline derivative with the conventional name "Indolinoren" on the state of the excretory function of the kidneys under the conditions of water and salt load. Materials and methods. Studies were performed on white non-linear rats. The water load was modelled by introducing distilled water (5 ml per 100 g of body weight of the animal); salt load - intragastric administration of 0.45 % sodium chloride solution in an amount of 3 % of body weight. Indolinoren and comparison drug furosemide were administered intragastrically at a dose of 29.5 mg / kg and 5 mg / kg, respectively. Results and discussion. It has been established that indolinoren has a saluretic effect in conditions of water load, accompanied by an increase in sodium excretion by 132 % and potassium by 2.4 %. Against the background of the introduction of indolinoren, a significant increase in the sodium-potassium coefficient of urine was established 2.3-fold (p <0.05), which indicates a more pronounced natriuresis than kaliuresis. Under conditions of salt load, indolinoren promotes a significant increase in urine output by 381 % (p <0.05), increases sodium excretion by 127 % (p <0.05), potassium by 7 %. There were no significant differences in creatinine excretion. The expression of diuretic activity in conditions of salt load indolinoren exceeds furosemide and does not have a significant difference under conditions of water load. Conclusion: The increase in natriuresis and, to a lesser extent, the kaliuresis, as well as the absence of significant changes in the excretion of creatinine, a glomerular filtration marker, on the background of the introduction of indolinoren indicates that its diuretic effect is realized due to oppression of tubular reabsorption. In the mechanism of indolinoren action involved inhibition of mineralocorticoid control of the excretory function of the kidney, as evidenced by the increase in the sodium-potassium coefficient of urine. The obtained data justify the need for further in-depth study of indolinoren as a perspective diuretic